PEMBERDAYAAN IBU HAMIL MELALUI YOGA PRENATAL TERHADAP PROSES PERSALINAN DI PRAKTIK MANDIRI BIDAN KOTA PALEMBANG TAHUN 2024 - Rohaya, Rohaya; Rosyati Pastuty,; Wilma, Wilma (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Prolonged labor remains a significant cause of maternal and neonatal mortality, often resulting from inadequate uterine contractions and fetal factors. Prenatal yoga has emerged as an effective complementary practice to address this issue by improving maternal physical, mental, and spiritual readiness for childbirth. This community empowerment program aimed to educate and encourage pregnant women in Palembang to practice prenatal yoga routinely under the guidance of independent midwifery practices. Conducted from August to October 2024, the program included educational sessions, hands-on yoga training, and pre- and post-intervention evaluations. Results revealed a marked improvement in participants' knowledge about prenatal yoga and labor processes, with the percentage of women exhibiting good knowledge increasing from 18.18% to 81.82%. Prenatal yoga effectively reduced discomfort during pregnancy, enhanced muscle strength and flexibility, and lowered stress and anxiety levels, contributing to shorter and smoother labor. These findings underscore the importance of integrating prenatal yoga into routine antenatal care to promote maternal and neonatal health outcomes